2018
DOI: 10.1149/2.1201802jes
|View full text |Cite
|
Sign up to set email alerts
|

Impedance Characterization of Chitosan Cytotoxicity to MCF-7 Breast Cancer Cells Using a Multidisc Indium Tin Oxide Microelectrode Array

Abstract: Chitosan is an amino polysaccharide with possible biomedical applications, for example, in bandage materials or as an antibacterial agent or a cytotoxic agent for tumor and cancer cells. In this study, the cytotoxic effect of chitosan (CTSN-P) on MCF-7 breast cancer cells was monitored in a nondestructive and real-time manner by electrical cell-substrate impedance sensing with a fabricated multidisc indium tin oxide electrode array. The electrical impedance characteristics of cell growth on the multidisc elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…Research using small working electrodes and interdigitated electrodes has shown that it is possible to monitor cells in two dimensional (2D) cultures using this technique. While small working electrodes have been used to monitor confluent cell cultures challenged with drugs, interdigitated working and reference electrodes have been shown to be more effective at monitoring cell proliferation across the well surface over time [ 7 , 10 , 25 , 30 ]. This highlights the importance of electrode configuration for monitoring cell cultures and the differences in their potential applications.…”
Section: Discussionmentioning
confidence: 99%
“…Research using small working electrodes and interdigitated electrodes has shown that it is possible to monitor cells in two dimensional (2D) cultures using this technique. While small working electrodes have been used to monitor confluent cell cultures challenged with drugs, interdigitated working and reference electrodes have been shown to be more effective at monitoring cell proliferation across the well surface over time [ 7 , 10 , 25 , 30 ]. This highlights the importance of electrode configuration for monitoring cell cultures and the differences in their potential applications.…”
Section: Discussionmentioning
confidence: 99%
“…At lower concentrations (12.5 mM) of the drug, cells are also in normal expanded morphology; however, at higher drug concentrations (37.5 mM) a large number of cells are rounded up and detached from the gold surface due to cell death as described in previous literature. 31,[47][48][49][50][51] Kustermann et al reported that a rise in impedance reveals cell proliferation however, a reduction can be reected as an insignia of cytotoxicity leading to death and detachment from the electrode surface. 47 Similarly, Wei et al also reported that with the increase of drug doses of doxorubicin, the cell death enhances which leads to the detachment of cells from the planer electrode areas.…”
Section: Cell Morphology Analysismentioning
confidence: 99%
“…It is examined that every matrix has its benefits and drawbacks; therefore, it is of great interest to develop new efficient novel matrices. Due to the presence of plentiful -NH 2 and -OH functional groups, it can easily react with bioactive molecules that results in a superior fabricating substrate for the covalent immobilization by means of covalent binding or electrostatic interactions (Park et al 2018). It demonstrates good quality adhesion characteristics in one of the study where it has been investigated for the development and adherence of well SNPs in the matrix of MWCNTs.…”
Section: Chitosan: Electrochemical Sensing Materialsmentioning
confidence: 99%